Métodos Anticonceptivos en mujeres en edad fértil .en el barrio Partido Alto de la ciudad de Tarapoto. Provincia Departamento y Región San Martín - Perú 1994 - Ramírez Rodas, Mery Graciela (1995)
This descriptive study with prospective data collection, performed in the Partido Alto neighborhood in the city of Tarapoto, Province, Region Department and San Martin Peru 1994 is a sample study where the research material were 503 women of childbearing age (15-49), who represent 18% of women enumerated. The objectives were: Identify contraceptive methods, demonstrate the total fertility rate as variables; describe the degree level of knowledge; identify: the main problems related to the use of contraceptive methods, the main sources of production and information and the group or type of users; demonstrate the intentions of future use of contraceptives by women aged 15-49 who do not use. The results were: The common method is the pill with 34.7%, followed by 23.2% IUD. It was determined that the total fertility rate is 2.7 children per woman and 96.9% of women of childbearing age know any contraceptive method. Most referrals were health problems (pain, discomfort, vaginal discharge, drops, bleeding) with 74.8% mostly related to the use of the pill. The sources of obtaining contraceptives were health facilities (MoH - IPSS) with 71.8%. By age, women aged 15-34 years used in higher percentage {73. 7%) of contraception; married reach the highest percentage with 49.9%; women with secondary and higher education account for 84% among those using; it was found that the surveyed women not using intend use of contraceptive methods in the future with 97% showing greater preference for the pill and the IUD. The reason that prompted us to undertake this research was to obtain in-situ information that enables individuals and institutions interested in population health and make settings with real basis and no population estimates, thus concluding the proposed objective problems.